The Diagnostic Value of Platelet Count and MPV in Suspected COVID-19 Patient at Dr. Saiful Anwar Hospital - Agustin Iskandar; Aditya Sri Listyoko; Hambiah Hari Oki (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
COVID-19 is a disease caused by SARS-CoV-2. Haematology alterations like lymphopenia is common, but not much study involves about thrombocyte. Incidence of thrombocytopenia in COVID-19 patient is 5-53.6%. Purpose of this study is to analyze diagnostic value of thrombocyte count and MPV in COVID-19. Cross sectional design took place at Dr. Saiful Anwar Hospital on March-June 2020. Data was taken at first admission. Confirmation test with SARS-CoV-2 gene detection with RT-PCR method. 115 patient suspected COVID-19 collected at the end of study with 69 positive and 46 negative. AUROC for thrombocyte is 0.336 (CI: 95%, 0.238 – 0.435, p= 0.01); MPV 0.488 (CI  95%, 0.378 – 0.598, p= 0.762). Thrombocyte count and MPV doesn't have good diagnostic value for COVID-19. This might be due to different conditions that patient might had at admission. Thrombocytopenia and increased MPV often caused by hyperinflammatory condition and severe infection as mentioned in other study. Thrombocyte count and MPV alone can't be used to diagnose COVID-19. Coincide use of other marker such inflammatory markers might be useful. Future study with larger sample and serial testing may needed to evaluate more about diagnostic value of thrombocyte count and MPV.